Fatigue Testing of a New Locking Plate for Hip Fractures - Hunt, Stephen; Martin, Rod; Woolbridge, Bryan (CMBES Proceedings, 2010)
Femoral neck subsidence and varus deformity can have a signiﬁcant effect on functional out- comes in patients with femoral neck fractures - particularly in the young trauma patient.   A new locking plate construct has been proposed as an alternative to address femoral neck fractures. New trauma products do not have set testing protocols which must be completed before clinical testing.  This study has been undertaken to investigate the biomechanical properties of the locking plate with speciﬁc reference to the fatigue performance of the new construct and, additionally, illustrate the challenges associated with development of a standardized pre-clinical testing model. The study consists of development of a testing strategy and three mechanical testing phases. Each of the testing phases compare the new plate construct against the current gold standard of three cancellous screws.  The ﬁrst phase of biomechanical testing involved cadaveric specimens, statically loaded, until ultimate failure of the construct.  The second phase used synthetic bone substitute, loaded dynamically, to determine the fatigue performance of the constructs.  The third phase is a cadaveric model intended validate previous data. Static testing revealed the new locking plate construct to withstand signiﬁcantly higher static loads before failure than the three cancellous screw technique.  Fatigue testing revealed that without compression across the fracture site, the locking plate had a shorter fatigue life than the 3-cancellous screw technique.   When the locking plate was installed with compression across the fracture site, its fatigue performance was equivalent to that of the 3 cancellous screw technique.  Results of this study have demonstrated that the proposed locking plate construct for hip fractures has superior static strength, and equivalent fatigue life as the currently accepted 3-cancellous screw tech- nique.  Biomechanical testing highlighted that compression across the fracture site is critical to fatigue performance of both constructs.  Further biomechanical testing is required to conﬁrm if the new locking plate design prevents subsidence and varus deformity  compared to the 3 cancellous screw technique.  Development of a preclinical testing strategy for trauma products requires an individual understanding of the intended application of the product, expected modes of failure and a thorough understanding of the productʼs service requirements.